Socialization of Earthquake Friendly House Planning with a Theme "Nagari is Resilient to Earthquake Disasters" in Nagari Kajai, West Pasaman Regency - Putra, Rusnardi Rahmat; Saputra, Dezy; Agung, M. Darma (CIVED, 2024)
West Pasaman Regency is an area that has a fairly large threat of earthquake and tsunami disasters. The 6.2 Mw West Pasaman earthquake that occurred on February 25 2022 was quite large and resulted in 25 people dying, 465 people being injured and at least 16,000 people being displaced. This earthquake was located on the slopes of Mount Talamau at a depth of 10 km which was triggered by the activity of the Semangko fault fault, precisely in the unmapped Talamau segment. Apart from the loss of life, another impact caused by this earthquake disaster was the large number of collapses in people's houses. People's houses that have simple construction have a greater potential for collapse compared to other buildings whose designs comply with existing regulatory standards. In general, people's houses are only built by builders who do not know the technicalities of building earthquake-friendly houses. Builders are the main key to the quality of housing construction in society, so more attention is needed from people who are experts in their field because it is in their hands that the structural strength of a house is built. The community service organized by the Institute for Research and Community Service (LP2M) Padang State University together with several Civil Engineering lecturers aims to channel their knowledge to the community, especially to builders to increase knowledge in building earthquake-friendly houses. This activity is also expected to reduce damage in the future if an earthquake occurs, which has been designed according to standards applicable in Indonesia. From the results of interviews with several builders and local residents, it turns out that their knowledge of the basic techniques for building earthquake-friendly houses is still limited. So that this outreach can provide a useful contribution to builders' knowledge of the basics of earthquake-friendly house construction.